Differentiating between perovskite and double perovskite nanocrystals - Mishra, Pritish (2023)
Perovskite structure takes the empirical formula ABX3, whereas Double perovskites, or elpasolites, are the crystal structures in which the B position in ABX3 is equally occupied by two different cations. The usual compositions of Double perovskite structure are (1-3) type double perovskites, which means that the two B cations have +1 and +3 oxidation states. In the quest of making near infrared emitting halide perovskite quantum dots, the most commonly and most productive method for colloidal synthesis of nanocrystals, the hot injection method, was used. Target composition for such an application was Cs2PbSnI6. The synthesis process was optimized for reactant ratios to achieve the exact stoichiometry. But then, the usual characterization processes, such as powder X-ray Diffraction, Selected area electron diffraction (SAED) and STEM-EDX were not enough to convincingly prove that the structure thus formed was a double perovskite. The STEM EDX results can only explain the overall atomic ratio of an ensemble of nanocrystals (with a little error) as the issue of carbon contamination dominates at single nanocrystal level. Whereas lack of reference crystal structure and low amount of formed product in each synthesis batch contribute to inconclusive results in SAED and XRD and fail to answer the question, “Is it even a double perovskite structure? Or just a perovskite structure with non-periodic substitution or an ensemble of different crystals of different compositions?”. This problem seems evident in the literature as there seems no mention of any (2-2) type double perovskite structure. Which makes this work first to mention the properties, characteristics, and problems with (2-2) type double perovskite nanocrystals. A combination of advanced electron microscopy techniques and advanced X-ray diffraction techniques such as PDF refinement were used to tackle this problem. Some sample preparation tips and tricks for characterization are also explained for such a distinction.